A Cognitive Analysis of De-Pragmatization in Sheikh Al-Waeli's Sermonic Style - Abd Hassan, Bushra (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study illustrates the de-pragmatization of metaphorical linguistic aspects in the sermonic style of Sheikh Ahmed Al-Waeli, a conspicuous Iraqi Shia theologian known for his distinctive rhetorical performance. This study illustrates Al-Waeli's sermons to classify forms of metaphor and observes the technique of de-pragmatization, when speeches lose their original pragmatic power due to conventionalization, semantic degradation, and re-contextualization. Therefore, the study uses a qualitative analysis of metaphorical expressions derived from Al-Waeli's sermons, improved by quantitative data concerning metaphor varieties and de-pragmatization procedures. The results designate that Al-Waeli's metaphorical aspect shows a sophisticated stability between conventional Islamic metaphors and novel practices, with contrasting topics of de-pragmatization in several sermon situations. Besides, the present study develops a thought of religious discourse via de-pragmatization procedures, while preserving religious integrity and communicative competence. Therefore, this research simplifies the rhetorical styles used in modern Islamic sermons and the linguistic mechanisms that enable the transference of religious beliefs across cultural and temporal restrictions. Keywords: De-Pragmatization, Islamic Philological Style, Metaphor, Sermonic Style, Sheikh Ahmed Al-Waeli